Patterns and drivers of dairy development in India: insights from analysis of household and district-level data - Kishore, Avinash; Birthal, P.S.; Joshi, Pramod K.; Shah, Tushaar; Saini, A. (Diva Enterprises Private Limited, 2016)
Traditionally, Indian farmers kept bovines, especially cattle, for draught purposes in agriculture and transportation with milk as an adjunct. However, with increasing farm mechanization and rising demand for milk, the bovine functions have shifted more towards dairying. While bovine population has been increasing, the chronic scarcity of feed and fodder reinforces the need for optimization of bovine population for sustainable growth of dairying. In this paper, using district-level data from 1997 to 2007, we show that this transformation from draught to dairying is underway in some parts of the country, and further using household-level data, we find that smallholders have contributed disproportionately more to this transformation. This transformation or intensification of dairying is demand-driven with urbanization having a strong positive influence on dairy development. On the supply-side, factors like farm mechanization, improved access to groundwater irrigation and crop diversification away from cereals, are associated with a shift in the bovine economy from draught to dairying.